2021
DOI: 10.1038/s41598-021-98089-3
|View full text |Cite|
|
Sign up to set email alerts
|

Biopsy bacterial signature can predict patient tissue malignancy

Abstract: Considerable recent research has indicated the presence of bacteria in a variety of human tumours and matched normal tissue. Rather than focusing on further identification of bacteria within tumour samples, we reversed the hypothesis to query if establishing the bacterial profile of a tissue biopsy could reveal its histology / malignancy status. The aim of the present study was therefore to differentiate between malignant and non-malignant fresh breast biopsy specimens, collected specifically for this purpose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…A good example of such a study design can be found in the paper of Plaza-Diaz and colleagues [273]. Along the same line, protocols for identifying external contaminations to the microbiome are very important [8,69,274], especially in samples with low biomass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A good example of such a study design can be found in the paper of Plaza-Diaz and colleagues [273]. Along the same line, protocols for identifying external contaminations to the microbiome are very important [8,69,274], especially in samples with low biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple microbial compartments undergo oncobiotic transformation during breast cancer, including breast tissue [55,56], milk ducts [57], the inherent microbiome of the breast carcinoma [54,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72], the distal gut [51,52,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89], and the urinary microbiome [54,90]. However, no differences in the microbiome of the nipple [57,69] and the oral microbiome [54] between healthy individuals and breast cancer patients have been detected. Besides bacteria, viruses (parapoxviruses [91], human papillomavirus [92], Herpesviridae, Retroviridae, Parapoxviridae, Polyomaviridae, Papillomaviridae [64]), fungi, and p...…”
Section: Oncobiosis In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, multiple labs have reported similar findings in various tumor types, but the need for improvements in methodology became apparent due to the difficult nature of ‘low bacterial biomass’ sample types involved and the need to eliminate potential sources of contamination. Prof. Tangney presented details from several recent papers from his group aimed at tackling this problem, through improvements in bioinformatics [ 10 ], sequencing [ 11 ], and sample processing aspects [ 12 , 13 ], in addition to improved protocols for sample acquisition [ 14 ].…”
Section: Microbiota and Cancer: What? So What? Now What?mentioning
confidence: 99%
“…The rationale for the title of his talk quickly became apparent, as he described ‘What’ as the characterization of the tumor microbiome [ 15 ], and ‘So What’ as studies on potential implications of bacterial presence, such as his group’s finding in 2015 that such bacteria enzymatically altered commonly used chemotherapeutic drugs in mouse models [ 16 ]. Finally, an example of ‘Now What’ was given with a description of exploitation of such findings in a biomarker context, describing a new study from his group where the development of a machine-learning strategy enabled the team to use the bacterial signature of fresh tissue biopsies to predict their malignancy status [ 14 ].…”
Section: Microbiota and Cancer: What? So What? Now What?mentioning
confidence: 99%